2013
DOI: 10.1093/toxsci/kft092
|View full text |Cite
|
Sign up to set email alerts
|

Glycidol Induces Axonopathy by Adult-Stage Exposure and Aberration of Hippocampal Neurogenesis Affecting Late-Stage Differentiation by Developmental Exposure in Rats

Abstract: To investigate the neurotoxicity profile of glycidol and its effect on developmental hippocampal neurogenesis, pregnant Sprague Dawley rats were given drinking water containing 0, 100, 300, or 1000 ppm glycidol from gestational day 6 until weaning on day 21 after delivery. At 1000 ppm, dams showed progressively worsening gait abnormalities, and histopathological examination showed generation of neurofilament-L(+) spheroids in the cerebellar granule layer and dorsal funiculus of the medulla oblongata, central c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
2
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 41 publications
(65 reference statements)
2
42
2
1
Order By: Relevance
“…may be caused by feedback control for anti-apoptosis in response to the reduction in the number of immature granule cells. Although we previously did not detect changes in cellular kinetics on cell proliferation and apoptosis by immunohistochemistry and the TUNEL-assay (Akane et al, 2013a), we could show the possibility of glycidol-induced suppression of cell proliferation and apoptosis in the dentate gyrus by microarray analysis. In the corpus callosum, which was selected to represent white matter tissues, we observed transcript upregulation of genes related to growth, survival and function of glial cells, i.e.…”
Section: Discussioncontrasting
confidence: 54%
See 4 more Smart Citations
“…may be caused by feedback control for anti-apoptosis in response to the reduction in the number of immature granule cells. Although we previously did not detect changes in cellular kinetics on cell proliferation and apoptosis by immunohistochemistry and the TUNEL-assay (Akane et al, 2013a), we could show the possibility of glycidol-induced suppression of cell proliferation and apoptosis in the dentate gyrus by microarray analysis. In the corpus callosum, which was selected to represent white matter tissues, we observed transcript upregulation of genes related to growth, survival and function of glial cells, i.e.…”
Section: Discussioncontrasting
confidence: 54%
“…Therefore, it may be reasonable to investigate developmental neurotoxicity in the hippocampal dentate gyrus using microarray techniques. We have recently revealed that dams of the present study exposed to glycidol at 1000 ppm induced axonal injury involving both central and peripheral nervous systems (Akane et al, 2013a). In the central nervous system, axonal injury was apparent in the cerebellum and medulla oblongata.…”
Section: Discussionmentioning
confidence: 51%
See 3 more Smart Citations